Improved therapeutic approach for spinal muscular atrophy via ubiquitination‐resistant survival motor neuron variant - Joonwoo Rhee; Jong‐Seol Kang; Young‐Woo Jo; Kyusang Yoo; Ye Lynne Kim; Sang‐Hyeon Hann; Yea‐Eun Kim; Hyun Kim; Ji‐Hoon Kim; Young‐Yun Kong (Wiley, 2024)
Abstract Background Zolgensma is a gene‐replacement therapy that has led to a promising treatment for spinal muscular atrophy (SMA). However, clinical trials of Zolgensma have raised two major concerns: insufficient therapeutic effects and adverse events. In a recent clinical trial, 30% of patients failed to achieve motor milestones despite pre‐symptomatic treatment. In addition, more than 20% of patients showed hepatotoxicity due to excessive virus dosage, even after the administration of an immunosuppressant. Here, we aimed to test whether a ubiquitination‐resistant variant of survival motor neuron (SMN), SMNK186R, has improved therapeutic effects for SMA compared with wild‐type SMN (SMNWT). Methods A severe SMA mouse model, SMA type 1.5 (Smn−/−; SMN2+/+; SMN∆7+/−) mice, was used to compare the differences in therapeutic efficacy between AAV9‐SMNWT and AAV9‐SMNK186R. All animals were injected within Postnatal Day (P) 1 through a facial vein or cerebral ventricle. Results AAV9‐SMNK186R‐treated mice showed increased lifespan, body weight, motor neuron number, muscle weight and functional improvement in motor functions as compared with AAV9‐SMNWT‐treated mice. Lifespan increased by more than 10‐fold in AAV9‐SMNK186R‐treated mice (144.8 ± 26.11 days) as compared with AAV9‐SMNWT‐treated mice (26.8 ± 1.41 days). AAV9‐SMNK186R‐treated mice showed an ascending weight pattern, unlike AAV9‐SMNWT‐treated mice, which only gained weight until P20 up to 5 g on average. Several motor function tests showed the improved therapeutic efficacy of SMNK186R. In the negative geotaxis test, AAV9‐SMNK186R‐treated mice turned their bodies in an upward direction successfully, unlike AAV9‐SMNWT‐treated mice, which failed to turn upwards from around P23. Hind limb clasping phenotype was rarely observed in AAV9‐SMNK186R‐treated mice, unlike AAV9‐SMNWT‐treated mice that showed clasping phenotype for more than 20 out of 30 s. At this point, the number of motor neurons (1.5‐fold) and the size of myofibers (2.1‐fold) were significantly increased in AAV9‐SMNK186R‐treated mice compared with AAV9‐SMNWT‐treated mice without prominent neurotoxicity. AAV9‐SMNK186R had fewer liver defects compared with AAV9‐SMNWT, as judged by increased proliferation of hepatocytes (P < 0.0001) and insulin‐like growth factor‐1 production (P < 0.0001). Especially, low‐dose AAV9‐SMNK186R (nine‐fold) also reduced clasping time compared with SMNWT. Conclusions SMNK186R will provide improved therapeutic efficacy in patients with severe SMA with insufficient therapeutic efficacy. Low‐dose treatment of SMA patients with AAV9‐SMNK186R can reduce the adverse events of Zolgensma. Collectively, SMNK186R has value as a new treatment for SMA that improves treatment effectiveness and reduces adverse events simultaneously.